Teaching Children to Read : The Fragile Link Between Science & Federal Education Policy - Gregory Camilli; Sadako Vargas; Michele Yurecko (Arizona State University, 2003)
Teaching Children to Read (TCR) has stirred much controversy among reading experts regarding the efficacy of phonics instruction. This report, which was conducted by the National Reading Panel (NRP), has also played an important role in subsequent federal policy regarding reading instruction. Using meta-analysis, the NRP found that systematic phonics instruction was more effective than alternatives in teaching children to read. In the present study, the findings and procedures leading to TCR were examined. We concluded that the methodology and procedures in TCR were not adequate for synthesizing the research literature on phonics instruction. Moreover, we estimated a smaller though still substantial effect (d = .24) for systematic phonics, but we also found an effect for systematic language activities (d = .29) and tutoring (d = .40). Systematic phonics instruction when combined with language activities and individual tutoring may triple the effect of phonics alone. As federal policies are formulated around early literacy curricula and instruction, these findings indicate that phonics, as one aspect of the complex reading process, should not be over-emphasized.